PENGARUH PARTISIPASI ANGGARAN, PARTISIPASI PERENCANAAN STRATEGIS DAN KOMITMEN ORGANISASI TERHADAP BUDGETARY SLACK - Agustianto, Aris Anugrah (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
This study aims to find empirical evidence about the effect of budget participation, participation in strategic planning, motivation, organizational commitment, budgetary slack. The sampling method used in this study was purposive sampling method and obtained 15 research samples as an observation item found in Banten Province. Data were analyzed using Partial Least Square (PLS) software. The results of this study indicate that the variable Budget Participation has a positive and significant effect on organizational commitment, participation in strategic planning has a positive and significant effect on organizational commitment, Motivation variables have a positive and significant effect on Organizational Commitment, Organizational commitment has a positive and significant effect on Budgetary Slack, Motivation has a negative effect against Budgetary Slack, Budget Participation has a positive and significant effect on Budgetary Slack.